Water-gated organic transistors on polyethylene naphthalate films - De Oliveira, Rafael Furlan [UNESP]; Casalini, Stefano; Cramer, Tobias; Leonardi, Francesca; Ferreira, Marystela; Vinciguerra, Vincenzo; Casuscelli, Valeria; Alves, Neri [UNESP]; Murgia, Mauro; Occhipinti, Luigi; Biscarini, Fabio (IOP Publishing, 2016)
Water-gated organic transistors have been successfully exploited as potentiometric transducers in a variety of sensing applications. The device response does not depend exclusively on the intrinsic properties of the active materials, as the substrate and the device interfaces play a central role. It is therefore important to fine-tune the choice of materials and layout in order to optimize the final device performance. Here, polyethylene naphthalate (PEN) has been chosen as the reference substrate to fabricate and test flexible transistors as bioelectronic transducers in liquid. PEN is a biocompatible substrate that fulfills the requirements for both bio-applications and micro-fabrication technology. Three different semiconducting or conducting polymer thin films employing pentacene, poly(3-hexylthiophene) or poly(3, 4-ethylenedioxythiophene):poly(styrenesulfonate) were compared in terms of transconductance, potentiometric sensitivity and response time. The different results allow us to identify material properties crucial for the optimization of organic transistor-based transducers operating in water.
Keywords: Flexible electronics; Organic bioelectronics; Polyethylene naphthalate; Water-gated organic transistors